The Description of Student Understanding about Elasticity Concept - Mustofa, Zainul (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
Different from the classical mechanic topic, student’s understanding related to matter elasticity has got less attention in research. This study aimed to expose student’s understanding related to conceptual problems in matter elasticity with descriptive quantitative research method. Subject consisted of 48 students of engineering with the computer and network competence in 2016/2017 academic year. The data was gathered using multiple choices test. The study concluded that student’s understanding related to elastic and plastic matter was good, but most students did not well understand about Hooke laws, the relationship in elasticity formula, and composition elastic matter. The study suggested further research to explore the causes of student’s difficulties.